2013
DOI: 10.1016/j.bbrc.2012.10.131
|View full text |Cite
|
Sign up to set email alerts
|

CYLD, a deubiquitinase specific for lysine63-linked polyubiquitins, accumulates at the postsynaptic density in an activity-dependent manner

Abstract: Polyubiquitin chains on proteins flag them for distinct fates depending on the type of polyubiquitin linkage. While lysine48-linked polyubiquitination directs proteins to proteosomal degradation, lysine63-linked polyubiquitination promotes different protein trafficking and is involved in autophagy. Here we show that postsynaptic density (PSD) fractions from adult rat brain contain deubiquitinase activity that targets both lysine48 and lysine63-linked polyubiquitins. Comparison of PSD fractions with parent subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…We have so far established that certain enzymes, a protein kinase CaMKII, a small G-protein regulator SynGAP and a deubiquitinase CYLD, redistribute in response to depolarization or NMDA application [8], [17], [16], [18], and that the movements of all three molecules are blocked upon inhibition of CaMKII [13], [10], [11]. …”
Section: Discussionmentioning
confidence: 99%
“…We have so far established that certain enzymes, a protein kinase CaMKII, a small G-protein regulator SynGAP and a deubiquitinase CYLD, redistribute in response to depolarization or NMDA application [8], [17], [16], [18], and that the movements of all three molecules are blocked upon inhibition of CaMKII [13], [10], [11]. …”
Section: Discussionmentioning
confidence: 99%
“…The PSD complex was defined as the postsynaptic specialization that comprises the electron dense PSD core and a network contiguous to it. The area of the PSD complex to be measured was outlined as described previously [9]. CYLD and p-CYLD labels appeared as individual black grains at the PSD complex, and immunolabeling intensity was expressed as the number of labels per μm length of the PSD.…”
Section: Methodsmentioning
confidence: 99%
“…Immuno electronmicroscopy (EM) on hippocampal cultures revealed that even though more CYLD accumulates at the PSD under excitatory conditions, the protein is also present at the synapse in the absence of stimulation, although at lower quantity [9]. We previously reported that CaMKII mediates NMDA-induced recruitment and activation of CYLD at the PSD [10], but the regulation of CYLD under basal conditions is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroscientific studies have indicated that CYLD accumulates in the postsynaptic density (PSD) and is thought to be involved in removing K-63 from PSD proteins, preventing their autophagic regulation [56]. This accumulation and lack of recycling may cause neurodegeneration [56].…”
Section: Cyld Overviewmentioning
confidence: 99%